The Passive Voice in the Ancient Egyptian Pyramid Texts I: The Passive with .t and .tj Suffix - Almansa-Villatoro, M. Victoria (Zeitschrift für ägyptische Sprache und Altertumskunde, 2024)
The present article studies the ancient Egyptian Pyramid Texts passive strategy with an added .t or .tj suffix, the so-called T passive. It sets out to be an analysis of its uses and an interpretation of its meaning. A comprehensive list of data is also provided, along with tables analyzing the number of occurrences of certain syntactic structure, and the number of instances of the same verb using other passive strategies. A consideration of the number of occurrences of every passive form and their distinct uses within the different corpora of texts (Sacerdotal and Personal Texts) determines possible grammatical differences between both sources.